2018
DOI: 10.9734/jalsi/2018/45192
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Ameliorative Effects of Annona muricata (Linn) on Sodium Fluoride-Induced Toxicity on Haematological Indices and Fecundity of Adult Male Wistar Rats

Abstract: Aim: Ameliorative potentials of Annona muricata (Linn) on Sodium fluoride-induced toxicity on haematology indices and fecundity of adult male Wistar rats. Methods: Eighty-five (85) adult male Wistar rats were divided into 17 groups of 5 rats each. NaF (10 mg/kg) + fruit juice, ethanol stem bark, and leaf extracts of A. muricata at five different doses of 500, 1000, 1500, 2000 and 2500 mg/kg body weight were administered to the rats for 6 weeks. Blood samples were taken after 6 weeks through the ocular puncture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Hormonal level of testosterone propionate-induced benign prostatic hyperplasia in male rats administered with aqueous leaf extract of C. pentandra showed a significant decrease (p > 0.05) in FSH levels for male rats in Groups 3 to 6 treated with C. pentandra compared to the negative control. This agrees with the study of Amadi et al [16] who investigated the potential ameliorative effects of aqueous leaf extract of C. pentandra. There was a decrease in testosterone and FSH concentrations in Groups 4 to 6 compared to the negative control.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Hormonal level of testosterone propionate-induced benign prostatic hyperplasia in male rats administered with aqueous leaf extract of C. pentandra showed a significant decrease (p > 0.05) in FSH levels for male rats in Groups 3 to 6 treated with C. pentandra compared to the negative control. This agrees with the study of Amadi et al [16] who investigated the potential ameliorative effects of aqueous leaf extract of C. pentandra. There was a decrease in testosterone and FSH concentrations in Groups 4 to 6 compared to the negative control.…”
Section: Discussionsupporting
confidence: 93%
“…The results of Amadi et al [16] who investigated the potential ameliorative effects of C. pentandra on sodium fluorideinduced toxicity on hematological indices and fecundity of adult male Wistar rats and discovered that leaf extracts of C. pentandra have no toxic effect on testes of male rats corroborated the findings of C. pentandra having no toxic effect on testes of male rats.. C. pentandra is antioxidative, anticancer, antimalarial, antihelmintic, piscicidal, antiviral, and antibacterial properties, implying a wide range of possible applications. Asimicin, bullatacin, and bullatalicin are three significant acetogenins found in ripe C. pentandra…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This could be attributed to the combined effects of TP and Alum on the tissue membrane of the treatment groups. In a similar study carried out by Amadi et al 2018 andOnyegeme-Okerenta et al (2022), it was observed that rats given Annona muricata extracts had lower levels of oxidative stress produced by sodium fluoride and testosterone propionate respectively. In Group 2, there was a substantial increase (p<0.05) in testosterone and FSH levels which support the findings of Morse et al (1972), who reported that testosterone propionate boosts plasma testosterone approximately twofold.…”
Section: Discussionmentioning
confidence: 81%
“…A significant decrease in haematology index was observed in group 2 when it was evaluated. A reduction in packed cell volume (PCV) and haemoglobin (Hb) suggests either erythrocyte destruction or decreased production, both of which can lead to anaemia (Amadi et al, 2018). The treatment with graded doses of Alum did not have any significant positive effect on the haemoglobin level of the experimental animals.…”
Section: Discussionmentioning
confidence: 99%